Robert Louis Stevenson - Gray, William. author. aut Link
XVI, 190 p.
Keywords: More than most writers, Robert Louis Stevenson requires a Literary Life. Fascination with Stevenson's life (the 'Stevenson biography' is almost a minor genre) has tended to eclipse his literary achievement. This study focuses on Stevenson's writing practice within the different geographical, cultural and political contexts that shaped it, from Scotland to the South Seas. Following Stevenson's own views on biography, the book is not structured primarily in terms of chronology, but is more a kind of literary geography than traditional literary history.